2000
DOI: 10.1074/jbc.m001462200
|View full text |Cite
|
Sign up to set email alerts
|

The Expression and Localization of Plasma Platelet-activating Factor Acetylhydrolase in Endotoxemic Rats

Abstract: The production of platelet-activating factor (PAF) and PAF-like phospholipids that also bind the PAF receptor are implicated in numerous pathological situations including bacterial endotoxemia and injury-induced oxidative damage. PAF and PAF-like phospholipids are hydrolyzed and inactivated by the enzyme PAF acetylhydrolase. In the intact rat, infusion of lipopolysaccharide (LPS) into a mesenteric vein served as an acute, liver-focused model of endotoxemia. We determined that the liver responds to LPS exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 26 publications
5
24
1
Order By: Relevance
“…Thus, the release of Lp-PLA 2 occurs independently of lipoprotein secretion; the enzyme subsequently associates with these particles ( 1 ). Lp-PLA 2 is actively produced and secreted by monocyte-derived macrophages in response to infl ammatory cytokines and microbial lipopolysaccharides (43)(44)(45)(46)(47). Hypercholesterolemic patients exhibit a low grade infl ammation, as is indicated by the higher hsCRP levels compared with controls, a fi nding that is in accordance with our previously published results ( 48 ).…”
Section: Discussionsupporting
confidence: 90%
“…Thus, the release of Lp-PLA 2 occurs independently of lipoprotein secretion; the enzyme subsequently associates with these particles ( 1 ). Lp-PLA 2 is actively produced and secreted by monocyte-derived macrophages in response to infl ammatory cytokines and microbial lipopolysaccharides (43)(44)(45)(46)(47). Hypercholesterolemic patients exhibit a low grade infl ammation, as is indicated by the higher hsCRP levels compared with controls, a fi nding that is in accordance with our previously published results ( 48 ).…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, an increase in plasma Lp-PLA 2 activity in patients with sepsis ( 54,55 ) or AIDS ( 21 ) has been reported. On the other hand, some studies showed that total plasma Lp-PLA 2 activity is decreased in sepsis ( 22,(56)(57)(58). In our study, total plasma Lp-PLA 2 and HDL-Lp-PLA 2 activities as well as the ratio of total plasma Lp-PLA 2 /ApoB did not signifi cantly differ between and PON1 (paraoxonase) activities was noticed ( Table 2 ).…”
Section: Pon1 (Paraoxonase) and Pon1 (Arylesterase) Activitiessupporting
confidence: 42%
“…In another study involving human non-adherent monocyte-macrophage cells (Mono-Mac 6; MM6) it was found that both PAF and LPS were able to up-regulate the expression of PAF AH in a dose dependent manner. The specific PAFR inhibitor WEB2170 was able to completely block the PAF stimulated up-regulation of PAF AH and also inhibited the PAF AH production in the tested cell line but also in rats (Howard & Olson, 2000), after LPS stimulation. The p38 MAPK inhibitor, SB203580 inhibited by 60% the up-regulation of PAF AH after LPS stimulation while PAF stimulation was not affected.…”
Section: Paf Levels and Paf Ah Lp-pla2 Expressionmentioning
confidence: 84%